Les « Partis populistes » face à l’évolution des systèmes partisan et politique : pour une sociologie politique comparative de l’histoire du populisme en France (1880-2002) - Fabien Nicolas (Amnis)
Since the end of the XIXth century, populist mobilizations are periodic datas in French politics. On the last presidential elections (April 21st 2002), the candidate of the populist party reaches the second turn. Consequently, we can wonder about the historical possibility of a real French populist party and about its action which would not be apprehended as mere historical time periods characterized by phenomena such as “boulangisme”, “poujadisme” or even the National Front. It is a real political power existing beyond charismatic leaders and systemic crisis, which requires both a political and sociological approach.